A hybrid assessment framework for human‐centred sustainable smart campus: A case study on COVID‐19 impact. Issue 3 (9th August 2022) - Yip, Christine; Zhang, Yuchen; Lu, Erwan; Dong, Zhao Yang
Abstract: The continuous development of modern information and communication technologies is driving the smart revolution in the global education system. The outbreak of the COVID‐19 pandemic has recently posed unprecedented challenges to educational institutes. The education informatisation technologies are playing a vital role to ensure the continuity and enhance the performance of education during the pandemic, which accelerates the integration of cutting‐edge technologies and thus the overall development of the smart campus. Alongside the technological advancement, the existing studies indicate that the success of smart campus development mainly depends on three key dimensions: technology capability, sustainability, and student health and well‐being. However, the state‐of‐the‐art assessment on smart campus are mostly unilaterally dependent but lack a balanced evaluation of the three dimensions. To bridge this gap, this paper proposes a hybrid assessment framework that integrates all three key aspects, aiming to provide a multi‐dimensional view of campus smartness for human‐centred sustainable development. The smart campus assessment index resulting from the proposed framework is constructed under a limiting factor formulation to jointly model the individual contributions from the three dimensions as well as their trade‐off relationship. The contribution from each dimension is the weighted normalised sum of a set of precisely selected indicators. A case study is also conducted on the historical data of a US university to investigate the effectiveness of the proposed framework and the assessment index in response to the COVID‐19 pandemic, which also demonstrates the rationality of the hybrid framework for smart campus assessment.